Factors associated with postoperative delirium after thoracic surgery - YILDIZELİ, BEDRETTİN; BEKİROĞLU, GÜLNAZ NURAL; BATIREL, HASAN FEVZİ (ELSEVIER SCIENCE INC, 2005)
Background. Postoperative delirium is an acute confusional state characterized by fluctuating consciousness and is associated with increased morbidity and mortality. We analyzed the incidence and risk factors of delirium following thoracic surgery. Methods. All patients (n = 432) who underwent thoracotomy or sternotomy from 1996 to 2003 were analyzed retrospectively. The diagnosis of postoperative delirium was based on Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Results. Postoperative delirium developed in 23 patients (5.32%) between postoperative days 2 to 12 (mean, 4.4 +/- 2.6 days). There were 15 males and 8 females, with a mean age of 59.4 years (24 to 77 years). The delirium group was older (59.4 +/- 14.6 vs 51.3 +/- 15.5 years, p < 0.01) and had a longer operation time than the nondelirious group (5.34 +/- 1.58 vs 4.38 +/- 1.6 hours, p = 0.005). Morbidity and mortality rates were not significantly different between the two groups (56.5% vs 47.1%; 13.0% vs 3.66%, respectively). Univariate analysis showed that the older age, markedly abnormal postoperative levels of sodium, potassium, or glucose, sleep deprivation, operation time, and diabetes mellitus were risk factors (p < 0.05). According to multivariate analyses, four factors were selected as predictive risk factors: (1) markedly abnormal postoperative levels of sodium, potassium, or glucose (p = 0.038); (2) sleep deprivation (p = 0.05); (3) age (p = 0.033); and (4) operation time (p = 0.041). Conclusions. Postoperative delirium may cause higher morbidity and mortality rates after thoracic surgery. Close postoperative follow-up and early identification of predisposing factors such as older age, sleep deprivation, abnormal postoperative levels of sodium, potassium, or glucose, and longer operation time can prevent occurrence of postoperative delirium. (C) 2005 by The Society of Thoracic Surgeons.
Keywords: GASTROINTESTINAL SURGERY; COGNITIVE DYSFUNCTION; VASCULAR-SURGERY; ELDERLY-PATIENTS; CARDIAC-SURGERY; RISK-FACTORS; PREVENTION; PREDICTION; DIAGNOSIS; PROGNOSIS